How Do Business Digitalisation, Organisational Leadership, Innovation, and Entrepreneurship Sustainability Interact? A Meta-Analysis Approach - Sahoo, Saroj Kumar; Caganova, Dagmar; Pattnaik, Laxmikant; Vartiak, Lukas; Sahu, Valavadra (European Journal of Sustainable Development, 2025)
This study explores the interrelationships among business digitalisation (BD), organisational leadership (OL), business innovation (BI), and entrepreneurship sustainability (ES) to assess whether synergistic effects exist and how they influence business sustainability outcomes. A mixed-method approach was applied, combining bibliometric techniques, such as citation analysis, frequency distributions, co-word analysis, co-occurrence mapping, and relational frequency matrices, with qualitative content analysis and conceptual synthesis. The dataset includes 311 peer-reviewed articles published between 2001 and 2023, drawn from Web of Science, SCOPUS, and selected grey literature, all focusing on at least one of the four constructs. Findings show strong evidence of multiple interconnections, particularly BD–OL and BI–BD, with Asia, especially India, demonstrating how leadership drives digitalisation and innovation. However, ES–BI and ES–OL remain underexplored, representing significant research opportunities. Results confirm BD as a key enabler across innovation and sustainability, often mediated by leadership and innovation dynamics. Implications suggest that policymakers should support integrated digital, leadership, and innovation frameworks to foster sustainable entrepreneurship, while business leaders are encouraged to invest in digital capabilities and innovation-driven leadership. Educational institutions should emphasise interdisciplinary training that integrates digitalisation, leadership, and sustainability. By highlighting overlooked connections and offering a global perspective, this study advances theoretical and practical understanding of sustainable digital entrepreneurship. Keywords: Business digitalisation; Organisational leadership; Business innovation; Entrepreneurship sustainability; Bibliometric analysis; Sustainable digital entrepreneurship